2009
DOI: 10.2174/138161209787354258
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Selected Cardiovascular Hormones on Arterial Stiffness and Wave Reflections

Abstract: The large conduit arteries of the thorax and abdomen are elastic while those in the arms and legs are muscular. Alterations in wall properties of elastic arteries occur over time and are usually permanent in nature; acute changes can, however, occur is response to a change in transmural pressure. Chronic alterations in properties of muscular arteries are minimal but changes (e.g vasoconstriction, vasodilation or tone) do occur in response to smooth muscle cell (SMC) stimulation. In general an increase in arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 189 publications
0
16
0
1
Order By: Relevance
“…37,38 Furthermore, it has been suggested that estrogen improves endothelial function. 12,39 Therefore, it is feasible that the premenopausal status of our participants may have influenced the beneficial effect of RET on arm vasodilatory capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Furthermore, it has been suggested that estrogen improves endothelial function. 12,39 Therefore, it is feasible that the premenopausal status of our participants may have influenced the beneficial effect of RET on arm vasodilatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…8 Chronic exercise, in particular, resistance exercise training (RET), has been suggested to improve endothelial function, [9][10][11] by increasing FBF and vasodilatory capacity, which in turn may decrease the AIx. Improving the arterial function is of clinical importance because an increased AIx imposes an overload to the left ventricle that promotes myocardial hypertrophy, 12,13 a main predictor of cardiovascular morbidity and mortality. 14 Acute upper-body resistance exercise increases FBF and vasodilatory capacity to reactive hyperemia (RH) in healthy young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness is regulated by numerous factors such as NO. Mean arterial pressure and structural changes in the components of the arterial wall were once thought to be the main determinants of arterial stiffness, however it is now recognized that arterial stiffness is also regulated by vascular tone and that endothelium derived mediators, such as NO, contribute to the functional regulation of arterial stiffness [6].…”
Section: Introductionmentioning
confidence: 99%
“…AS results from the complex interplay between several independent and interdependent factors. Aging is considered to be the most important risk factor for the development of AS alongside other various changes in hemodynamic forces, salt intake, glycemic control and the overall decline in the cellular function [6][7][8][9] . In the arterial wall, aging and increased blood pressure leads to stiffening via medial degeneration that presents with fractures and fragmentation of the elastic lamellae, increased collagen and calcium content, dilation and hypertrophy of the large arteries 10) .…”
Section: Arterial Stiffness and Ckd: General Considerationsmentioning
confidence: 99%